2016
DOI: 10.4067/s0717-97072016000200023
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Organophosphorus Complexes and Structural Charaterization of Two Dimeric Triphenylphosphinne Complexes of Mercury(ii) Ions From Dimeric Complexes of [4-Methylbenzoylmethylenetri-P-Tolylphosphine Mercury(ii) Halides

Abstract: The organophousphorus complexes of [(PPh 3) 2 Hg 2 Cl 4 ] (4), [(PPh 3) 2 Hg 2 Br 4 ] (5) and [(PPh 3) 2 Hg 2 I 4 ] (6) were resulted from nucleophilic substitution of triphenylphosphine ligand with trip -tolylphophine complexes (1-3). The crystal structures of two organophousphorus complexes of mercury(II) ions 4 and 6 have been determined by means of the X-ray diffraction. Both complexes were crystallized in the monoclinic space groups P2(1)/c, and have very similar bond lengths, angles pattern and same subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The sp 3 hybridized Hg (II) ion in the complex 1 adopted a tetrahedral coordination environment with one short Hg-I bond at distance 2.6745(6) Å, one Hg-P bond at distance 2.4739(17) Å and two asymmetric bridging Hg-I bonds at distances 2.8397(6) and 2.9539(6) Å. The internuclear distances between mercury atoms were found to be 3.911(2) Å, which was much longer than the sum of van Der Waals radius (1.50 Å) of the two mercury atoms [35,48]. This indicated that the absence of significant bonding interactions between the mercury atoms in the molecular structure of complex 1.…”
Section: The Complex 1 Is Stabilized By C-h•••i Interactions (C9-h9•••i4mentioning
confidence: 88%
See 2 more Smart Citations
“…The sp 3 hybridized Hg (II) ion in the complex 1 adopted a tetrahedral coordination environment with one short Hg-I bond at distance 2.6745(6) Å, one Hg-P bond at distance 2.4739(17) Å and two asymmetric bridging Hg-I bonds at distances 2.8397(6) and 2.9539(6) Å. The internuclear distances between mercury atoms were found to be 3.911(2) Å, which was much longer than the sum of van Der Waals radius (1.50 Å) of the two mercury atoms [35,48]. This indicated that the absence of significant bonding interactions between the mercury atoms in the molecular structure of complex 1.…”
Section: The Complex 1 Is Stabilized By C-h•••i Interactions (C9-h9•••i4mentioning
confidence: 88%
“…The organophosphorus complexes 1, 2, and 3 have been synthesized as white crystalline solids by the reaction of HgX2 (X: I, Br, and Cl) and PPh3 in 1:1 proportion in good yield in acetonitrile medium (Scheme 1). Earlier, Dadrass et al [35] reported the syntheses of these complexes, but their synthetic methods were more tedious and less economical. These had been prepared by the nucleophilic substitution reaction of triphenylphosphine ligand with tri(p-tolyl)phosphinehalide complexes using dry solvent methanol and diethyl ether, and recrystallized from chloroform diethyl ether.…”
Section: Synthesis Aspects Of the Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…LUMO and HOMO energy and gap energy give expression of the chemical action of molecules, and the molecule which has a small gap energy (LUMO-HOMO) can be linked to high chemical reactivity [47]. The dipole moment (µ) is used to find out the molecules polarity, when the electronegativity of atoms increases, the value of dipole moment increases too [48]. Due to the data in Table 1, we found that the EAB compound has a high stability and chemical activity capability.…”
Section: Optimization and Energies Calculationsmentioning
confidence: 99%
“…The framework's total energy consists of internal, potential, and kinetic energies [66]. The high value of total energy signifies the better stability of compounds.…”
Section: Optimizations and Energies Calculationsmentioning
confidence: 99%